Factors Influencing Postgraduate Students’ Investment Awareness - Bonansyah, Albert; Chairina, Chairina (Journal of Accounting Science, 2025)
General Background: Investment awareness refers to an individual's willingness and ability to manage current resources for future benefits. Specific Background: In Central Kalimantan, investment awareness remains very low, with only 3.47% of the population engaged in investment activities. Knowledge Gap: Among postgraduate students, the level of awareness is even lower, at only 0.95%. Objective: This study aims to partially and simultaneously analyse the influence of financial experience, social media, financial literacy, personal interest, and environmental factors on investment awareness. Methods: This study involved 132 postgraduate students from the State Islamic Institute of Palangka Raya and Palangka Raya University, with 119 valid responses. Data were collected through a Likert scale questionnaire and analysed using SmartPLS 4.1 through out-of-model and in-model assessments and hypothesis testing. Results: Findings indicate that all independent variables significantly and positively influence investment awareness, both individually and collectively. Gender as a control variable shows a significant positive effect, income has a significant negative effect, and age does not have a significant impact. Novelty: This study provides new insights by incorporating financial experience and social media as key variables, alongside gender, age, and income as control variables, within the context of postgraduate students in Palangka Raya. Implications: The results highlight the importance of strengthening financial experience and financial literacy to promote informed investment behaviour from an early stage.